2006
DOI: 10.1108/00907320610716413
|View full text |Cite
|
Sign up to set email alerts
|

Collaborations for success: high school to college transitions

Abstract: PurposeThe paper seeks to provide an overview of innovative high school to college collaborations and initiatives at Kent State University Library. These collaborations and initiatives may serve as models and resources for future academic library high school to college programs.Design/methodology/approachNew and innovative collaborations and initiatives aimed at fostering successful high school to college student transitions are discussed.FindingsProvides overview of the K‐12 educational environment in Ohio, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 6 publications
(1 reference statement)
0
29
0
Order By: Relevance
“…Benefits of collaboration between school and academic libraries can include decreased library anxiety, as advocated by Mellon (1986), enhanced visibility of the participating libraries in their communities, and a demonstration of their value as partners in education. It is also suggested that instructional outreach to high schools can assist with recruiting and promote higher education as a whole (Burhanna & Jensen, 2006;Cosgrove, 2001). As Burhanna and Jensen state, "collaboration can be a powerful pathway to improving student preparation and success across the K-20 educational continuum" (p. 518).…”
Section: K Angell and E Tewellmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits of collaboration between school and academic libraries can include decreased library anxiety, as advocated by Mellon (1986), enhanced visibility of the participating libraries in their communities, and a demonstration of their value as partners in education. It is also suggested that instructional outreach to high schools can assist with recruiting and promote higher education as a whole (Burhanna & Jensen, 2006;Cosgrove, 2001). As Burhanna and Jensen state, "collaboration can be a powerful pathway to improving student preparation and success across the K-20 educational continuum" (p. 518).…”
Section: K Angell and E Tewellmentioning
confidence: 99%
“…The body of LIS literature contains myriad examples of higher education institutions which have initiated library instruction partnerships with local public schools (Bruch & Frank, 2011;Zoellner & Potter, 2010;Collins, 2009;Lee, Morris, Brazell, & Turner, 2007;Burhanna & Jensen, 2006;Evans, 1997). These colleges and universities have made it a priority to serve the information needs not only of the campus community but also to expand their expertise and resources to members of the surrounding geographical community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• preparing students for college level research; • supporting the development of critical thinking skills; • assisting students with their high school research (Cosgrove, 2001); • decreasing student anxiety through visits to a large academic library (Burhanna & Jensen, 2006); • developing information literacy skills and encouraging lifelong learning (AASL/ACRL, 2000); • fostering relationships and connections at an academic library and institution; and (Ury, 1996a); and • building relationships with academic and local high school educators.…”
Section: About the Collaboration Nahs Was Founded In 2004 Through An mentioning
confidence: 99%
“…The "new generation of computer-literate undergraduates and the vast amount of information available by way of computers and electronic resources has increased the necessity for the development of [information literacy and] critical thinking skills" (Whitmire, 1998, p. 267). Bolstering student information literacy skills while they are still in high school has been a practice of many academic librarians through collaborative instructional outreach during the last 20 years (Burhanna & Jensen, 2006). "Declining retention rates, rising levels of remediation, [and] funding shortfalls" involving college freshmen reinforce the need to intervene (Burhanna & Jensen, 2006, p. 510).…”
Section: Introductionmentioning
confidence: 99%
“…Carr & Rockman (2003) encouraged academic librarians to "…work with their K-12 colleagues in enabling students to succeed in college" (p. 52) and cited several ongoing high school to college transition projects. Others reported on grant-funded initiatives, like the work of the Institute for Library and Information Literacy Education (ILILE) at Kent State University, which has recently developed several high school to college transition collaborations in Ohio (Burhanna & Jensen, 2006).…”
Section: Introductionmentioning
confidence: 99%